Pemanfaatan Sumber Daya Lingkungan Lokal Untuk Meningkatkan Hasil Belajar Siswa - Dwi Oktavia Ramadhani; Evi Nur Afifah; Fitri Zakiyatun Nisak (Kampus Akademik Publiser, 2025)
This research aims to evaluate the use of local environmental resources in an effort to improve student learning outcomes. The local environment-based learning approach provides students with the opportunity to understand academic concepts through direct experience that is relevant to everyday life. The method applied is classroom action research (PTK), which includes the stages of planning, implementation, observation and reflection. The research subjects were elementary school students in certain areas. Data was collected through observation, interviews and learning outcomes tests. Research findings show that the use of local environmental resources, such as flora, fauna, culture, and geographic potential, is able to increase student participation, foster awareness of environmental responsibility, and deepen their understanding of academic concepts. The increase in learning outcomes can be seen from the increase in the average student score in each cycle as well as the positive response to this learning method. The use of local environmental resources has proven to be effective in creating meaningful, contextual and relevant learning. Therefore, integrating local resources in learning can be an innovative strategy to improve student learning outcomes while supporting environmental conservation efforts. This study recommends that teachers creatively utilize local resources as media and sources of sustainable learning.